Lexical Meaning of Medical Terms Found in English Book End of Days: Predictions and Prophecies about the End of the World - Fitria, Tira Nur (Vivid: Journal of Language and Literature, 2023)
The purpose of the study is to find out the number of medical terms found in the book End of Days and to know the lexical meaning of medical terms found in the book End of Days. The method used in this research is the descriptive qualitative research method. Based on the analysis, the researcher found there are 220 medical terms found in the book End of Days Chapter VII with the sub-theme The End of Days through My Eyes. There are medical terms that show the name of diseases or disorders, the name of the place, part of the body, and other related medical terminology. The writer also translates the lexical meaning by using Dictionary of Medical Terms by Peter Collin and Dictionary of Medical Acronyms and Abbreviations by Stanley Jablonski to translate the acronyms and abbreviations of the medical term in the English book of The End of Days. There are many acronyms found in the book. Based on the results of the analysis of lexical meaning, the researcher concludes that the book has a variety of uniqueness in the content because the writers Sylvia Browne with co-writer Lindsay Harrison include medical terms in the book.